Respon Pertumbuhan Bibit Salak (Salacca Zallaca) terhadap Dosis Spora Endomikoriza pada Media Pembawa Pasir Kuarsa dan Zeolit - ARYANI, NI KADEK; RAI, I NYOMAN; MAYADEWI, NI NYOMAN ARI (Agrotrop : Journal on Agriculture Science; Vol 10 No 1 (2020), 2020)
Response of Salak Seedlings ( Salacca Zallaca ) Growth to Dosage of Endomycorrhizal Spore in Quartz Sand and Zeolite Carrier Media. This study aimed to study the effect of endomycorrhizal spore dosage and carrier media that were applied directly to the roots of salak plants. The research designed as factorisl by using Randomized Block Design with 2 treatment factors. The first factor was number of endomycorrhiza spores consists of 4 levels i.e 0, 75, 150, and 225 spores per 500 g carrier media per polybag, while the second factor was the type of carrier media consist of 2 levels i.e zeolite and quartz sand. The results showed that interaction between endomycorrhizal spore dosage with   carrier   media   did   not   significantly   influence   the   growth   of   salak   seedlings. Endomycorrhizal spores in doses of 75, 150 and 225 spores per polybag increased root infection and leaf P nutrient content compared to control, but seed height, leaf area, shoot dry weight, root dry weight and total dry weight of seedlings not significantly difference. The zeolite carrier media caused root infection by mycorrhizal was higher than quartz sand media, but the P nutrient uptake and seedling growth were not significantly different. Based on the results of this study it is necessary to make a longer observation of the effect of endomycorrhizal spore doses and carrier media on the growth of salak seedlings.